Magnetorresistência túnel ressonante e acoplamento magnético em heteroestruturas epitaxiais - Varalda, José (Universidade Federal de São Carlos, 2004)
In the context of spin electronics, this doctorate thesis presents an experimental study of spin polarized transport in epitaxial heterostructures as planar magnetic tunnel junctions formed by semiconductors and metallic ferromagnets. It was demonstrated that the epitaxial Fe/ZnSe/Fe structures fabricated by molecular beam epitaxy have the microscopic and macroscopic properties necessary for application in magnetic tunnel junctions. The experimental observation of antiferromagnetic coupling in these structures indicates strongly that samples are free of pinholes for barrier thickness down to 25 Å. Spin polarized transport studies using microjunctions demonstrated that the conductance mechanism is the resonant tunneling via defect states in the barrier, reinforcing the idea anticipated theoreticaly that the transport depends on the magnetic tunnel junction structure as a whole. This result is general since defect states near the Fermi energy are expected for semiconductor and insulanting barriers, pointing out the importance of their roles in the understanding of the spin polarized tunneling phenomena. The study of growth properties associated with magnetic properties made possible the use of MnAs films as current polarizer electrode in magnetic tunnel junctions. Experiments exploiting magnetic phase transition were also realized for these MnAs films. Our first results of spin polarized transport in a Fe/ZnSe/MnAs presented a tunnel magnetoresistance variation of 10 %, indicating that MnAs can transmit spin polarized electrons across a ZnSe barrier.
Keywords: Física do estado sólido; Magnetorresistência túnel ressonante; Acoplamento magnético; Heteroestruturas epitaxiais; CIENCIAS EXATAS E DA TERRA::FISICA